Changes in the Dynamics of Living Weight and Growth of Sur Karakul Sheep by Etological Types in the Conditions of Northern Karakalpakstan - Akhmet Abdirazakovich Urimbetov (American Journal of Botany and Bioengineering, 2026)
This article examines the live weight and growth dynamics of Sur Karakul sheep raised in the extreme natural and climatic conditions of Northern Karakalpakstan, broken down by ethological types. During the study, the live weight indicators of sheep from birth until the separation of lambs and the lambing period, as well as the characteristics of absolute, relative, and daily growth, were analyzed. The results showed that sheep of the 1st ethological type prevailed in terms of live weight and growth indicators across all periods, and this advantage was found to be statistically significant. It was also observed that the growth rate of the live weight of the sheep varied depending on the physiological periods, i.e., growth accelerated in the period following the separation of the lambs. Based on the results obtained, it was substantiated that it is possible to increase the productivity of Karakul sheep by improving selection and breeding work based on ethological types.